Occupational Anxiety among Adolescents with Motor Disability in Jordan in Light of Some Variables - Majali, Areen A. Q. Bajes Al Jadeed (Journal of Ecohumanism, 2024)
This study evaluated the level of occupational anxiety that exists among motor disability adolescents in Jordan while also assessing the impact that demographic characteristics like gender and parent education system, educational facility type and financial status, and academic performance and residential conditions play in adolescent anxiety. The research evaluated 100 adolescents between 13 and 18 years of age who received motor disability clinical diagnoses through purposive sampling from different public and private educational institutions. The research design was descriptive correlational, and a structured questionnaire contained demographic variables. It was also a modified version of Zaleski’s (1996) Future Anxiety Scale. Cronbach’s alpha value revealed strong internal consistency on the scale, with a rating of 0.87.The subjects demonstrated mid-level occupational anxiety according to their mean score of 60.31, with a standard deviation of 10.49. The subjects experienced their highest anxiety when measuring their skill suitability for employers (M = 3.16, SD = 1.30), along with performance confidence (M = 3.13, SD = 1.40) and concerns about judgments because of their disability (M = 3.12, SD = 1.29). Any differences in gender anxiety levels (t = -0.402, p = 0.690) and educational institutions (t = -1.704, p = 0.093) were statistically insignificant. One-way ANOVA tests showed that parental education levels matched equally across study participants with F = 0.046 while maintaining p = 0.833. The analysis showed that grade (β = -0.31, p = 0.698), together with family income (β = 0.0014, p = 0.676) and housing condition (β = -1.75, p = 0.515), did not predict occupational anxiety. The results from Pearson correlation coefficients demonstrated that occupational anxiety showed no important relationship with academic performance (r = -0.03, p = 0.844), family income level (r = 0.05, p = 0.669), or household size (r = 0.11, p = 0.327).